Peculiar Features of Pressure Jump in Steam-Water Injectors - A. V. Korolyev (Известия высших учебных заведений и энергетических объединенний СНГ: Энергетика, 2009)
The paper presents a criteria dependence for calculation of steam jet characteristics which is blown in cold water. Evaluations have been carried out and relations of technological and geometrical characteristics of steam-water injectors have been determined in the paper. The paper gives dependence evaluation of acoustic overpressure value and characteristic frequencies of injector’s «vibro-activity».